Paul and the resurrected body : social identity and ethical practice - O'Reilly, Matt, Dr (Emory studies in early Christianity, 2020)
"In Paul and the Resurrected Body: Social Identity and Ethical Practice, Matt O'Reilly makes the case that the social dimension of future bodily resurrection is just as important, if not more so, than individual salvation and resurrection. Through a close reading of key texts in the letters to the Corinthians, Romans, and Philippians, O'Reilly argues that resurrection is integral to Paul's understanding of Christian social identity. In Paul's theological reasoning, a believer's hope for the future depends on being identified as part of the people of God who will be resurrected"--